Organ donation and the teenage perspective: factors to consider regarding consent - Hodgson, Margie Cisneros, author; Makela, Carole, advisor; Buchan, Victoria, advisor; Kees, Nathalie, committee member; Quijano, Louise, committee member (Colorado State University. Libraries, 2015)
The purpose of this study was to understand the factors that teenagers consider when granting consent to become an organ donor for the first time. Ninety-seven participants completed a 31-item survey that included areas of knowledge, source of information, personal experience, willingness, and consent. Least square means and Chi-square were used to compare groups (e.g., experimental/control, pre-survey/post-survey) regarding consent. Other variables that were explored included; gender, ethnicity, religion, grade point average, and parent level of education. The intervention consisted of basic information regarding organ donation, a video entitled No Greater Love, and small group discussion regarding various donor/recipient scenarios. Findings indicated that increased knowledge does not always lead to consent, nor does knowing a donor (living or deceased) or someone on the waitlist influence consent among adolescents. The results suggested that teenagers do not have a good understanding of the topic of organ donation nor do they see themselves as living donors. Teens may not fully understand the implications and ramifications of their decision to be a donor when receiving a driver’s permit or license for the first time. This study brought to light factors that teens take into consideration when deciding to become an organ donor.